Investigating variations in the deep-sea sourcing strategies of car manufacturers: Two case studies of parts consolidation centers in Japan. Issue 2 (June 2020) - Itoh, Hidekazu; Guerrero, David
Highlights: In this paper the deep-sea sourcing strategies of car manufactures are explored. More than 30 semi-structured in-depth interviews have been carried out with manufacturers, auto-parts' suppliers and logistics providers in Japan. They use parts consolidation centers (PCCs), which are cross-docking facilities where parts are sorted and packed in sea containers depending on their final destination, for efficient distant sourcing. The PCCs play different roles within the logistics organization of them because of significantly different relationships with suppliers and wider differences in their overall logistics systems. Abstract: This paper investigates how two Japanese car manufacturers organize their shipments of auto-parts from suppliers located in Japan to their overseas assembly plants. It reveals that, in addition to the well-known differences such as specific manufacturer-supplier relationships or production strategies, the organization of logistics itself constitutes a basis for persistent variations. Car manufacturers operating at a global scale are facing uncertainties in matching supply and demand, thus increasingly requiring flexibility. This flexibility is notably achieved through varying combinations of local and distant sourcing to respond to changes in market conditions, currency exchange rates, and so on. To limit the costs of distant sourcing, car manufacturers use parts consolidation centers, which are cross-docking facilities where parts are sorted and packed in sea containers depending on their final destination. Findings show that, beyond its generic purpose, the parts consolidation centers play different roles within the logistics organization of the two focal firms. In one case, they are highly integrated within the global production system; in the other, they are simply used as transfer points. These different models of utilization of parts consolidation centers imply significantly different relationships with parts' suppliers, and point to wider differences in the overall logistics systems.